Dynamic changes of optical aberrations during restoration of optical properties of hydrophobic acrylic intraocular lens ejected through cartridge. Issue 8 (13th April 2015) - Uchida, Atsuro; Inoue, Makoto; Bissen-Miyajima, Hiroko; Hirakata, Akito
Abstract : Aim: To evaluate the effect of temperature on the restoration of the optical properties of hydrophobic acrylic intraocular lenses (IOLs) after ejection through a cartridge into a temperature-controlled water chamber. Methods: Acrylic IOLs (SA60AT; iSert 251; W-60; X-70; and VA-70AD) were loaded into a cartridge with viscoelastic material and ejected into a water chamber at 24°C or 34°C. A wavefront analyser was used to measure the spherical and cylindrical powers, and the higher-order aberrations of the optics of the IOLs. The time to restore the cylindrical power to within 0.1 dioptres of the baseline power was determined. Results: Surface irregularities of the IOLs after ejection were detected in the dioptric power maps but not in the higher-order aberration maps. The cylindrical power and the astigmatic and coma aberrations recovered immediately at 34°C but were delayed at 24°C. The restoration time of all IOLs at 24°C was significantly longer than that at 34°C (p<0.05). Conclusions: The dioptric power maps determined by the wavefront analyser can detect and follow the restoration of the optical properties of hydrophobic acrylic IOLs immediately after ejection. The restoration time was dependent on the temperature of the water chamber.